Collection of data sources from the HALO research aircraft for the HALO-(AC)^3 field campaign, March/April 2022 - André Ehrlich; Felix Ament; Clemantyne Aubry; Susanne Crewell; Henning Dorff; Florian Ewald; Geet George; Andreas Giez; Silke Groß; Lutz Hirsch; Friedhelm Jansen; Benjamin Kirbus; et al. (PANGAEA, 2024)
HALO-(AC)^3 is a field study that aimed at investigating Arctic air mass transformations by collecting a comprehensive observational data set in March and April 2022. A series of cases of warm air intrusions into the Arctic and marine cold air outbreaks were observed. Larger spatial scales were covered with a particular emphasis on process studies of important examples of Arctic mid-latitude linkages by applying the High Altitude and Long Range Research Aircraft (HALO), and the AWI polar aircrafts P5 & P6 for coordinated research flights over the Arctic. Simultaneously, observations at the AWIPEV station Ny Alesund were intensified and linked to the airborne activities including measurements of the tethered balloon system called BELUGA. The general objectives of the HALO-(AC)^3 mission were: 1) To perform quasi-Lagrange observations of air-mass transformation processes during meridional transports with a particular focus on pronounced warm air intrusions and marine cold air outbreaks, and 2) To test the ability of numerical atmospheric models to reproduce the measurements, which then can be applied to investigate the linkages between Arctic amplification and mid-latitude weather. This is the collection of datasets for all data obtained with research aircraft HALO.